Meritocracy in the legal professional academic field: reform of the accreditation, registration and evaluation systemLeadership and law - Bermúdez-Tapia, Manuel (2023)
In Peru, there isn't a single system for evaluating a professional profile, accreditation, registration, and career assessment in the field of law. It's possible to find sub-levels and entirely separate and exclusive procedures in the academic, professional, and specialization information recording. This applies to entities like SUNEDU, Renacyt, and even within the institutions under the Ministry of Labor, Servir, and other related departments. Given this landscape, an evaluation based on empirical evidence is presented, as reported in common media within the academic and professional sphere of lawyers. This paints a negative perspective on the meritocracy validation process, which seems to be bound by intricate procedures that ultimately distort this objective, significantly harming the lawyer's work, economic, and personal development.